Understanding the Rise in Corporate Cash: Precautionary Savings or Foreign Taxes - Faulkender, Michael W; Hankins, Kristine W; Petersen, Mitchell A (Review of Financial Studies, 2019)
Abstract What has driven the dramatic rise in U.S. corporate cash? Using non-public data, we show that the run-up is not uniform across firms but is concentrated in the foreign subsidiaries of multinational firms. Standard precautionary motives explain only domestic cash holdings, not these burgeoning foreign cash balances. Falling foreign tax rates, coupled with relaxed restrictions on income shifting, are the root of the changing foreign cash patterns. Firms with intellectual property have the greatest ability to shift income to low tax jurisdictions, and their foreign subsidiaries are where we observe the largest accumulations of cash. Received September 6, 2017; editorial decision August 22, 2018 by Editor David Denis. Authors have furnished an Internet Appendix, which is available on the Oxford University Press Web site next to the link to the final published paper online.